PERKEMBANGAN GURU PROFESIONAL DI ERA REVOLUSI INDUSTRI 4.0 - Aprillinda, Mutiara (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The development of the world is entering the era of industrial revolution 4.0. or the fourth world industrial revolution where technology has become the basis of human life. Everything becomes limitless and unlimited due to the development of the internet and digital technology. Therefore there are 4 stages of teacher professional development, namely: 1. Pre-professional era, 2. Autonomous professional era, 3. Collegiate professional era and 4. Professional era. In the era of the Industrial Revolution, the role of teachers was increasingly high and optimal.